Intercropping and cover crop effects on maize nitrogen requirement for optimal growth - Souza, S. S. [UNESP]; Flores, J. A. [UNESP]; Coelho, A. P. [UNESP]; Deienno, J. M. [UNESP]; Lemos, L. B. [UNESP]; Rolim, G. S. [UNESP] (Cambridge Univ Press, 2022)
Intercropping maize (Zea mays L.) with cover crops (Crotalaria spectabilis and Urochloa ruziziensis) is a sustainable cultivation strategy that can generate ecological benefits combined with grain yield (GY). However, cover crops may require nitrogen (N) fertilization management to be adjusted to obtain a high GY in intercropping systems. This study was carried out over 2 years in southeastern Brazil using randomized complete block design in a split-plot scheme. The plots were composed of three cropping systems: sole maize, maize + U. ruziziensis and maize + C. spectabilis. The subplots consisted of four N levels: 0, 70, 140 and 210 kg/ha. The GY of the maize + U. ruziziensis may be reduced by 13% compared to the sole maize. The GY of the sole maize increased up to 11.3 Mg/ha for 95 kg/ha of N in the first year and 6.7 Mg/ha for 169 kg/ha of N in the second year. The GY of the maize + U. ruziziensis intercropping system showed linear increments of 120 kg/ha for every 10 kg/ha of N applied. In the maize + C. spectabilis intercropping, GY increased up to 9.8 Mg/ha for 201 kg/ha of N in the first year, without any variation during the second year. The land equivalent ratio (LER) of intercropping was increased by more than 35% compared to that of sole maize, and N fertilization increased the LER of the sole maize and maize + U. ruziziensis intercropping. Maize intercropping had higher LER values with greater demand for nitrogen to obtain similar yields compared to sole maize cropping.
Keywords: Crotalaria spectabilis; grain yield; Urochloa ruziziensis; Zea mays L